Contribution of focal haemorrhage and microvascular fibrin deposition to fatal envenoming by Russell's viper (Vipera russelli siamensis) in Burma. - Than-Than; Francis, N; Tin-Nu-Swe; Myint-Lwin; Tun-Pe; Soe-Soe; Maung-Maung-Oo; Phillips, R; Warrell, D (1989)
In Burma, clinicopathological studies were carried out in three young farmers who died 15, 52 and 36 h after being bitten by Russell's vipers. Clinical features included local swelling, spontaneous systemic bleeding, defibrination, shock, cardiac arrhythmia, hypoglycaemia, coma and oliguria. On admission to hospital, 15, 48 and 21 h after the bites, serum venom antigen concentrations ranged from 50 to 130 ng/ml. Autopsies revealed widespread congestion and bleeding in the lungs, gastrointestinal and renal tracts, adrenals, heart, brain and anterior pituitary. There was histopathological evidence of focal haemorrhage and fibrin deposition at the site of the bite and in the pituitary, lungs and kidneys and acute tubular necrosis. Deposition of fibrin microthrombi results from the action of venom procoagulants. Shock was attributed to increased capillary permeability, revealed clinically by conjunctival oedema. Acute pituitary/adrenal failure in one case was explained by fibrin deposition and haemorrhage in the anterior pituitary--resembling Sheehan's syndrome. Acute tubular necrosis resulted from ischaemia caused by fibrin deposition and to prerenal factors. An intractable cardiac tachyarrhythmia may have been caused by subendocardial and myocardial haemorrhages.